Determinants of Firm Value: Analysis on Non-Cyclical Consumer Companies - Mardiana, Karlin Sagita; Attamimi, Abdul Hakim; Saud, Yehezkiel Victor; Sofianti, Evin (Asian Journal of Management Analytics, 2024)
This study evaluates the factors that affect the value of non-cyclical consumer companies listed on the Indonesia Stock Exchange. The factors tested consist of financial factors, namely tax planning and avoidance, profitability, and liquidity. Testing is also carried out on non-financial factors, namely gender diversity of the board of directors and good corporate governance. The population in this study were all Consumer Non-Cyclical companies listed on the Indonesia Stock Exchange for the period 2023. Sampling using purposive sampling system and obtained 34 companies. The data used is secondary data in the form of annual financial reports of companies listed during the period 2018 - 2022. This study uses panel data regression analysis. The study results state that firm value is positively impacted by financial variables and negatively impacted by non-financial variables.